Repere conceptuale privind formarea competențelor la geografie prin studierea orizontului local / ținutului natal [Articol] - Sochircă, Vitalie (CEP USM, 2021)
În articol sunt prezentate unele repere conceptuale privind formarea competențelor la Geografie în învățământul general prin studierea orizontului local / ținutului natal. Sunt puse în evidență prevederile Curriculumului Național la Geografie cu referire la studierea orizontului local / ținutului natal, într-o relație de continuitate directă cu prevederile similare ale curriculumului pentru educaţie timpurie și, respectiv, pentru învățământul primar.

The article presents some conceptual guidelines on the formation of competences in Geography in general education by studying the local horizon / homeland. The provisions of the National Curriculum in Geography with reference to the study of the local horizon / homeland are highlighted, in a direct continuity relationship with the similar provisions of the curriculum for early education and, respectively, for primary education.
CONCEPTUAL GUIDELINES REGARDING THE FORMING OF COMPETENCES IN GEOGRAPHY BY STUDYING THE LOCAL HORIZON / HOMELAND
Keywords: curriculum; competențe; orizont local; ținut natal; caracterizare geografică